2013
DOI: 10.1002/anie.201305154
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Copolymerization of CO2 with meso‐Epoxides Mediated by Dinuclear Cobalt(III) Complexes: Unprecedented Enantioselectivity and Activity

Abstract: Unprecedented enantioselectivity and catalytic activity was observed in the asymmetric copolymerization of CO2 with meso-epoxides (including the less reactive cyclopentene oxide) mediated by the dinuclear Co(III) complex (S,S,S,S)-1 under mild conditions. The resultant copolymers possess more than 99 % carbonate linkages and a perfectly isotactic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 220 publications
(177 citation statements)
references
References 51 publications
4
168
2
3
Order By: Relevance
“…Recently, we developed a chiral catalyst system based on the biphenol-linked dinuclear Co(III) complex (Fig. 1), which exhibited excellent activity, unprecedented enantioselectivity and molecular-weight control for the alternating copolymerization of CO 2 with mesoepoxides such as CPO under mild reaction conditions 25 . Previously, Coates and co-workers [26][27][28] have demonstrated that the dinuclear cobalt complexes based on binaphthol linker were highly active and enantioselective for homopolymerization of terminal epoxides.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a chiral catalyst system based on the biphenol-linked dinuclear Co(III) complex (Fig. 1), which exhibited excellent activity, unprecedented enantioselectivity and molecular-weight control for the alternating copolymerization of CO 2 with mesoepoxides such as CPO under mild reaction conditions 25 . Previously, Coates and co-workers [26][27][28] have demonstrated that the dinuclear cobalt complexes based on binaphthol linker were highly active and enantioselective for homopolymerization of terminal epoxides.…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity for cyclic carbonate formation toward exclusive polymer formation in the coupling between an epoxide and CO 2 can be achieved by replacing the binary system for a bifunctional analogue. This feature was demonstrated by Lu and coworkers using Co(salen) derived catalyst, and its binary and bifunctional derivative were evaluated in terms of chemo-selectivity behavior in the asymmetric copolymerization of CO 2 and epoxides [75].…”
Section: Cyclohexyl Salensmentioning
confidence: 91%
“…25) [94]. For CPO/CO 2 copolymerisation (25 C, 20 bar CO 2 ), in the presence of PPNX (X ¼ 2,4-dinitrophenoxide), complexes 17a-b were highly enantioselective (ee >99%) and highly active (TOF, 200 h À1 ).…”
Section: Linked Bimetallic Salen Complexesmentioning
confidence: 98%